2019
DOI: 10.1108/rjta-10-2018-0058
|View full text |Cite
|
Sign up to set email alerts
|

Colour management in circular economy: decolourization of cotton waste

Abstract: Purpose -While aiming to create methods for fibre recycling, the question of colours in waste textiles is also in focus; whether the colour should be kept or should be removed while recycling textile fibre. More knowledge is needed for colour management in a circular economy approach.Design/methodology/approach -The research included the use of different dye types in a cotton dyeing process, the process for decolourizing and the results. Two reactive dyes, two direct dyes and one vat dye were used in the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…• Closing resource loops: this cluster includes CF practices implemented with an aim to keep materials in the economy, Closed-loop recycling, a process where unwanted resources and products are collected, recycled, and then used again to make the same product it came from, and thus to create a circular flow of resources • Recycling for manufacturing a same product type (e.g., recycling polyester fabrics to polyester yarn for the same fashion item production) 42 (44.7%) Al Faruque et al, 2019;Bloomfield & Borstrock, 2018;Bocken et al, 2017;Bukhari et al, 2018;Cattermole, 2018;Corvellec & Stål, 2019;Daddi et al, 2019;do Amaral et al, 2018;Earley, 2017;Earley, 2019;Fischer & Pascucci, 2017;Franco, 2017;Goldsworthy & Ellams, 2019;Haslinger et al, 2019;Holtström et al, 2019;Hu et al, 2018;Hussain, 2018;Hvass & Pedersen, 2019;Karell & Niinimäki, 2019;Koszewska, 2018;Leal Filho et al, 2019;Määttänen et al, 2019;…”
Section: Practicesmentioning
confidence: 99%
See 2 more Smart Citations
“…• Closing resource loops: this cluster includes CF practices implemented with an aim to keep materials in the economy, Closed-loop recycling, a process where unwanted resources and products are collected, recycled, and then used again to make the same product it came from, and thus to create a circular flow of resources • Recycling for manufacturing a same product type (e.g., recycling polyester fabrics to polyester yarn for the same fashion item production) 42 (44.7%) Al Faruque et al, 2019;Bloomfield & Borstrock, 2018;Bocken et al, 2017;Bukhari et al, 2018;Cattermole, 2018;Corvellec & Stål, 2019;Daddi et al, 2019;do Amaral et al, 2018;Earley, 2017;Earley, 2019;Fischer & Pascucci, 2017;Franco, 2017;Goldsworthy & Ellams, 2019;Haslinger et al, 2019;Holtström et al, 2019;Hu et al, 2018;Hussain, 2018;Hvass & Pedersen, 2019;Karell & Niinimäki, 2019;Koszewska, 2018;Leal Filho et al, 2019;Määttänen et al, 2019;…”
Section: Practicesmentioning
confidence: 99%
“…Enablers that can support fashion stakeholders to further promote CF Chadegani et al, 2013;Bocken et al, 2017;do Amaral et al, 2018;Earley, 2017;Earley, 2019;Franco, 2017;Goldsworthy & Ellams, 2019;Hall & Velez-Colby, 2018;Holtström et al, 2019;Hvass & Pedersen, 2019;Kjaer et al, 2019;Leal Filho et al, 2019;Määttänen et al, 2019;Norris, 2019a;Pal et al, 2019;Pedersen et al, 2019;Raebild & Bang, 2017;Sandvik & Stubbs, 2019;Smith et al, 2017;Stål & Corvellec, 2018;Valentine et al, 2017;Vehmas et al, 2018; Knowledge support…”
Section: T a B L Ementioning
confidence: 99%
See 1 more Smart Citation
“…vinylsulfone groups in Remazol dyes) (Mahapatra 2016). Overall, reactive dyes can withstand color removal treatments better than direct dyes (Määttänen et al 2019), and colorants with anthraquinone units in particular were shown to have a high tolerance towards commercial laundering and oxidative bleaches (Bigambo et al 2018). To a certain degree, the strong covalent bonding of reactive dyes also tends to cross-link the cellulose structure, which can affect the final solubility of colored cellulose waste in ionic liquids or NMMO (Chattopadhyay 2011).…”
Section: Textile Dyesmentioning
confidence: 99%
“…The inhomogeneous constitution of cotton-rich waste material demands both its purification and tuning of the properties for achieving dissolution. Target of the pre-treatments is to remove non-cellulosic substances such as metals, ash, dyes, and residues of textile finishing chemicals, and to adjust the degree of polymerisation (DP) of the cellulose chains (Määttänen et al 2019). Thus, the quality of pretreated cotton-rich material meets the properties of commercial dissolving pulps.…”
Section: Introductionmentioning
confidence: 99%